Patterns and predictors of compliance with utilization management guidelines supporting a state policy to improve the quality of youth mental health services - Mora Ringle, Vanesa A. (Child Youth Serv Rev, 2018)
Despite a need to improve community mental health services for youths, little is known about compliance with state policies created to improve the quality of services in these settings. This study examined rates, patterns, and predictors of compliance with utilization management guidelines developed by the state of Texas to support a public health policy based on empirical evidence of effective mental health services (i.e., an evidence-based policy). Compliance was defined as authorizing policy-recommended service packages, whereas policy “overrides” occurred when recommended service packages were not authorized. The study sample consisted of 688 youths from ethnically and economically diverse backgrounds. Clinics reported that forty-six percent of youths were not authorized the policy-recommended service package. Overrides were primarily based on level of intensity. Most often, authorized services were less intensive than those recommended by the state guidelines. Higher severity at intake across multiple indicators was associated with authorizing less intensive services than what the policy guidelines recommended. Future studies evaluating system-level efforts such as state mental health policies should pay close attention to levels of service intensity, and their relation to the needs of youth in community settings.